Priorities in Health - Jamison, Dean T.; Breman, Joel G.; Measham, Anthony R.; Alleyne, George; Claeson, Mariam; Evans, David B.; Jha, Prabhat; Mills, Anne; Musgrove, Philip (Washington, DC: World Bank, 2012)
This companion guide to Disease Control Priorities in Developing Countries, second edition, speeds the diffusion of life-saving knowledge by distilling the contents of the larger volume into an easily read format. Readers will get an overview of the messages and analysis in Disease Control Priorities in Developing Countries, second edition; be alerted to the scope of major diseases; learn strategies to improve policies and choices to implement cost-effective interventions; and locate chapters of immediate interest.